(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article explores the integration of genomic data into personalized medicine within oncology, emphasizing its significant impact on improving cancer treatment outcomes. The analysis highlights how next-generation sequencing (NGS) technologies enable the identification of actionable mutations, facilitating tailored therapies that enhance efficacy and optimize healthcare resource allocation. Evidence indicates that personalized treatments lead to improved survival rates and quality of life for patients, particularly in specific cancer types. However, the article also addresses challenges related to healthcare disparities and emphasizes the need for equitable access to genomic testing. Future research directions are proposed to enhance the integration of genomic data into clinical practice and address issues of accessibility and data interpretation.